KONSEP PENDIDIKAN ISLAM DALAM AL-QUR’AN SURAH AL-ALAQ AYAT 1-5 (Telaah Pemikiran Quraish Shihab dalam Tafsir Al-Mishbah) - Abu Bakar , Abd. Syukur (Inspiratif Pendidikan, 2022)
This journal discusses the concept of Islamic education in the Koran surah Al-Alaq verses 1-5 (a study of the thoughts of Quraish Shihab in the interpretation of al-Misbah). This study aims to analyze: The concept of Islamic education in the Qur'an surah Al-Alaq verses 1-5 (a study of the thoughts of Quraish Shihab in the interpretation of al-Misbah), basically this research is a qualitative research with the type of library research with an approach philosophical history. The data sources used are primary data sources which are the main data sources that are directly related to the object of research including QS Al-Alaq verses 1-5 and the interpretation of al-Misbah then secondary sources include books or documents that support and complement the data primary data. The data collection method in this study is documentation. The data analysis technique used is descriptive analysis. The results of this study indicate that there are three concepts of children's education in surah Al-Alaq verses 1-5 according to Quraish Shihab, namely: 1) Tawhid Education (faith), 2) Skills education, 3) Intellect education, and 4) Psychology Education